1988
DOI: 10.1128/jvi.62.3.810-817.1988
|View full text |Cite
|
Sign up to set email alerts
|

N-ethylmaleimide inhibition of the DNA-binding activity of the herpes simplex virus type 1 major DNA-binding protein

Abstract: The major herpes simplex virus DNA-binding protein, designated ICP8, binds tightly to single-stranded DNA and is required for replication of viral DNA. The sensitivity of the DNA-binding activity of ICP8 to the action of the sulfhydryl reagent N-ethylmaleimide has been examined by using nitrocellulose filter-binding and agarose gel electrophoresis assays. Incubation of ICP8 with N-ethylmaleimide results in a rapid loss of DNA-binding activity. Preincubation of ICP8 with single-stranded DNA markedly inhibits th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This is the first report of the Chromatography of HSV DNA polymerase, ICP8, and UL37 proteins on SS DNA-agarose. HSV-1-infected cell proteins were isolated by the procedure of Ruyechan (33). Polymerase assays and immunoblots were performed as described in Materials and Methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first report of the Chromatography of HSV DNA polymerase, ICP8, and UL37 proteins on SS DNA-agarose. HSV-1-infected cell proteins were isolated by the procedure of Ruyechan (33). Polymerase assays and immunoblots were performed as described in Materials and Methods.…”
Section: Discussionmentioning
confidence: 99%
“…For studies involving the DNA synthesis inhibitor PAA, cells were infected and maintained in the presence of 300 ,ug of PAA per ml. For SS DNA-binding studies, protein extracts were prepared essentially as previously described (33). Briefly, CV-1 cells were infected at a multiplicity of infection of 10, and at 24 hours postinfection (HPI), the infected cells were scraped, pelleted, and quick frozen at -70°C.…”
Section: Construction Of Recombinant Plasmids Plasmid Prb210mentioning
confidence: 99%
“…Data from other systems indicate that redox regulation can play a role in the function of DNA-binding factors. This has been observed with transcriptional factors (reviewed in (Bauer et al, 1999;Kim et al, 2002)) and some other SSB proteins including the eukaryotic protein RP-A (You et al, 2000), herpes simplex virus -1 (HSV-1) protein ICP8 ( Knipe et al, 1982;Ruyechan, 1988;Dudas and Ruyechan, 1998), and baculovirus LEF-3 (Mikhailov et al, 2005). Similar to ICP8 and LEF-3, the DBP activities were also inhibited by alkylation with NEM.…”
Section: Discussionmentioning
confidence: 74%
“…The ability of ICP8 to interact with nucleic acids has been the subject of extensive study since its initial identification. Work from many laboratories has shown that ICP8 binds preferentially and cooperatively to single-stranded DNA (2,13,42,(45)(46)(47)(48)(49). This interaction is reminiscent of, although not identical to, that observed with the T4 gene 32 protein and the Escherichia coli single-strand-DNA-binding protein, based on results of agarose gel electrophoresis and electron microscopy.…”
mentioning
confidence: 87%